Cytotoxic Effects of Cananga odorata Essential Oil on p53 Protein and TP53 Gene Dynamics in Non-Melanoma Skin Cancer - Anuar, Muhammad Ashraf Fithri; Zamani, Muhammad Razin; Aminuddin, Amirul Hakim; Wan Omar, Wan Fatein Nabeila; Mohd Radzuan, Hazulin (HIBISCUS PUBLISHER, 2024)
Skin cancer remains one of the most common cancers worldwide. Cananga odorataessential oil (CO EO) has shown potential anticancer and antioxidant properties, suggesting its application as a topical treatment for skin cancer. The objective of this study is to assess the cytotoxic effect of CO EO on non-melanoma skin cancer, TP53 gene expression, and p53 protein expression. The methodology involves HFF1 (human foreskin fibroblast) and A431 (human epidermoid squamous carcinoma) cell lines treatment with CO EO at 125, 250, and 500 μg/mL for 24 h. Morphological changes were observed under light microscopy. p53 protein expression and secretion were assessed using western blot. TP53gene expression was quantified using real-time PCR. Our results show that CO EO treatment caused dose-dependent morphological changes in A431 cells, with increased non-viable cells observed. There was a 1.3-fold increase in p53 protein secretion in A431 cells treated at 250 μg/mL of CO EO. TP53 gene expression in A431 cells was significantly downregulated at 125 μg/mL (p= 0.03), while in HFF1 cells, TP53 was upregulated. To conclude, CO EO demonstrates cytotoxic effects on A431 cells, associated with altered p53 protein secretion and TP53 gene expression. Further studies are needed to elucidate its molecular mechanisms and therapeutic potential